2016
DOI: 10.1080/17446651.2017.1256199
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates in the treatment of osteoporosis: a review of skeletal safety concerns

Abstract: The use of bisphosphonates in treatment of osteoporosis declined significantly over the past decade. There is currently great concern, among patients and physicians, about two potential skeletal adverse effects associated with bisphosphonates- jaw osteonecrosis and atypical femur fractures. This has become a major public health issue since untreated osteoporosis carries a significant burden in terms of fracture-related morbidity and mortality, and bisphosphonates, considered first-line therapy for osteoporosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Ostlund et al [ 32 ] found that dissolved organic matter (DOM) limited Hg uptake from water by fish, yielding lower BCF. Higher concentrations of Hg in the leaves were measured in the contaminated areas compared to the remote areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ostlund et al [ 32 ] found that dissolved organic matter (DOM) limited Hg uptake from water by fish, yielding lower BCF. Higher concentrations of Hg in the leaves were measured in the contaminated areas compared to the remote areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BP treatment presents advantages, BPs have a long half-life of approximately 10 years in the human body. Therefore, further research is warranted to confirm the long-term side effects of BPs, including skeletal toxicity and osteonecrosis [ 214 ].…”
Section: Therapeutic Interventions For Vc In Patients With Ckdmentioning
confidence: 99%
“…However, it is becoming evident that although these drugs are effective in stopping the resorption of bone and preventing osteoporosis in women, they have a low long-term compliance [23]. Furthermore, bisphosphonates induce oxidative stress [24], associated with decreased glutathione and increased lipid peroxidation end-product malondialdehyde (MDA) [25], which are probably contributing factors to atypical fractures and osteonecrosis of the jaw, two debilitating complications of bisphosphonate treatment [26][27][28][29][30][31]. Indeed, treating cultured oral fibroblasts with bisphosphonates has demonstrated increased ROS levels [32], while oxidative stress has been detected in patients with bisphosphonate-related osteonecrosis of the jaw, accompanied by an increased oxidized glutathione (GSSG)/glutathione (GSH) ratio [33].…”
Section: Introductionmentioning
confidence: 99%